Acute and developmental toxicity assessment of erincine A-enriched Hericium erinaceus mycelia in Sprague–Dawley rats. (2nd October 2018) - Li, I-Chen; Chen, Wan-Ping; Chen, Yen-Po; Lee, Li-Ya; Tsai, Yueh-Ting; Chen, Chin-Chu
Abstract: This study aimed to establish an in vitro model to confirm the efficacy of erinacine A-enriched Hericium erinaceus (EAHE) mycelia and investigate its potential adverse effects in a preclinical experimental setting, including an assessment on the oral administration of EAHE mycelia in acute and prenatal developmental toxicity tests. At a single dose of 5000 mg/kg body weight, EAHE mycelia elicited no death or treatment-related signs of toxicity in ten Sprague–Dawley rats of both sexes during the 14 days of the experimental period. After considering the recommended dose range of EAHE mycelia from the acute toxicity test as well as the therapeutic doses, EAHE mycelia was administered to 66 pregnant rats in the low, medium, and high-dose groups by gavage at 875, 1750, and 2625 mg/kg body weight, respectively. All dams were subjected to a Caesarean section on the 20th day of pregnancy, and the fetuses were examined for any morphological abnormalities. Results indicated that weight of uterus, fetal body weight, number of corpora lutea, implantation sites, pre-implantation loss, and post-implantation loss of the treatment groups and the control group exhibited no statistical difference. In addition, no significant differences were observed in the fetal external, organ, and skeletal examinations. Taken together, it can be concluded that EAHE mycelia is considered safe and practically nontoxic for consumption within the appropriate doses and investigation period in this study.